Characteristics and Outcomes of Drainage Versus Surgery First in Severe Pancreatitis. Issue 9 (September 2020) - Harfouche, Melike; Clark, Jaclyn; Kim, Kevin; Bruns, Brandon; Diaz, Jose J.
Background: Percutaneous drainage as the initial procedure for severe pancreatitis (SP) may not always be optimal. Our aim was to identify the characteristics of patients who failed percutaneous drainage and compare their outcomes with patients who underwent surgical intervention as the initial approach. Methods: A retrospective review of a prospectively collected emergency general surgery registry of patients admitted to a tertiary-care, academic center with the diagnosis of SP who underwent an intervention was performed (2010-2018). Patients were divided into successful drainage (SD), drainage failure (DF), and surgery first (SF) groups. DF was defined as the need for surgical intervention. Results: The study included 129 patients. Fifty (38.8%) patients underwent SF as their initial management modality. Among 79 patients who underwent drainage, 34 (43.0%) were in the DF group and progressed to surgical intervention. Within that group, 19 (55.9%) underwent open necrosectomy. The DF group was more likely to have lower rates of peripancreatic fluid collections, a higher rate of necrotizing pancreatitis, and a higher Acute Physiology and Chronic Health Evaluation (APACHE) II score when compared with the DS group. Mortality was higher in the DF and SF groups, and total length of stay and ICU length of stay were highest in the DF group. Discussion: Patients who experience failure of drainage for SP have high morbidity and mortality rates and fare worse overall than patients who undergo surgery as the primary intervention. Patients with necrotizing pancreatitis and a higher APACHE II score might warrant surgical intervention over a drainage-first approach.